Iridium‐Catalyzed β‐C(sp2)−H Borylation of Enamides – Access to 3, 3‐Dihalogeno‐2‐methoxypiperidines. Issue 2 (14th January 2022) - Gillaizeau, Isabelle; Dondasse, Ismaël; Nicolas, Cyril; Mimoun, Liliane; Sukach, Volodymyr; Meudal, Hervé
Abstract: An efficient catalytic preparation of synthetically useful new β‐borylated enamides was achieved under relatively mild conditions via a regioselective iridium‐catalyzed C(sp 2 )−H borylation. The method features broad substrate scope, good functional group tolerance and efficient scale‐up. These C‐3 borylated enamides can be advantageously exploited in cross‐coupling reactions and converted into valuable 3, 3‐dihalogeno‐2‐methoxypiperidines in very short reaction times. Abstract : An efficient iridium‐catalyzed C( sp 2 )−H reaction of non‐aromatic tertiary enamides was successfully developed under mild reaction conditions and with high regioselectivity, leading to original C‐3 borylated enamides in good yields. These derivatives could then be exploited in Suzuki cross‐coupling reactions, or converted into valuable 3, 3‐dihalogenopiperidine derivatives through short reaction times with moderate to good yields.